Determining the efficiency of techniques for optimizing the number of tags in modern human-machine interfaces under conditions of limited resources - Polupan, Vladimir; Mirkevich, Roman; Pupena, Alexander; Klymenko, Oleh; Mirkevich, Oleksii (My University, 2024)
One of the challenges in creating SCADA/HMI-based solutions can be the number of tags (variables) in the runtime environment. A large number of tags can lead to a problem of limited available resources. The technique presented here allow for the optimization of the number of tags used in Human-Machine Interface systems built with SCADA software and operator panels in combination with Programmable Logic Controllers (PLCs). An evaluation of the efficiency of techniques for reducing the number of HMI tags was conducted on an experimental configuration consisting of objects such as discrete input/output, analog input/output, actuators such as valves with discrete/analog control, and drives with frequency converters. The optimization coefficient, defined as the ratio of the number of input/output tags used directly to the number of tags after applying the optimization principle, was used as the efficiency criterion. Depending on the techniques and their combinations, the criterion values reached orders of 4, 10, and in one case even more than 100. These values are explained by the application of multiplexing approaches and various packing techniques. The advantages and disadvantages of the reported techniques, as well as their application limitations, have been identified. Some techniques are suitable only for specific tasks. Однією з проблем у створенні рішень на основі SCADA/HMI може бути кількість тегів (змінних) у середовищі виконання. Велика кількість тегів може призвести до проблеми обмежених доступних ресурсів. Представлена тут методика дозволяє оптимізувати кількість тегів, що використовуються в системах людино-машинного інтерфейсу, побудованих за допомогою програмного забезпечення SCADA та панелей оператора в поєднанні з програмованими логічними контролерами (ПЛК). Оцінку ефективності методів зменшення кількості тегів HMI було проведено на експериментальній конфігурації, що складається з таких об'єктів, як дискретний вхід/вихід, аналоговий вхід/вихід, виконавчі механізми, такі як клапани з дискретним/аналоговим керуванням, та приводи з перетворювачами частоти. Як критерій ефективності використовувався коефіцієнт оптимізації, який визначається як відношення кількості тегів входу/виходу, що використовуються безпосередньо, до кількості тегів після застосування принципу оптимізації. Залежно від методів та їх комбінацій, значення критерію досягали порядків 4, 10, а в одному випадку навіть більше 100. Ці значення пояснюються застосуванням підходів мультиплексування та різних методів упаковки. Було визначено переваги та недоліки описаних методів, а також обмеження їх застосування. Деякі методи підходять лише для певних завдань.
Keywords: кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка; human machine interface; tag; resource optimization; tag licensing; інтерфейс людино-машина; тег; оптимізація ресурсів; ліцензування тегів